Page 52 - E-Modul Persamaan dan Pertidaksamaan Linear Satu Variabel
P. 52

KUNCI JAWABAN
                  Latihan soal 1


                                                                          3
                       1. a. 12x + 10 =− 4 − 2x                 2.c  15  − =  6
                                                                     4         
                           12x + 2x =− 4 − 10
                                                                             15    3          6
                                                                         4y     −     = 4y ×
                           14x =− 14                                          4    y          y
                           x =−1                                             15y − 12 = 24

                                                                             15 = 24 + 12

                                                                                     36
                                                                                 y =
                                                                                     15
                                     12                         2. d  2            1
                       1. b. x + 3 =                                    6  − 9 =      4  − 8
                                     5                                3            2
                           5(x + 3) = 12                                    4x − 6 = 2x − 4

                           5x + 15 = 12                                    4x − 2x =− 4 + 6

                           5x = 12 − 15                                          2x = 2
                               3                                                      2
                           x =                                                   x =
                               5                                                      2

                                                                                 x = 1
                                                                       1       5
                       2. a. 2 3x − 7 = 6 − 4x                  3. − = +
                                                                   2   3   3   6
                                  6x − 14 = 6 − 4x                          x   1        x   5
                                                                         6    −    = 6    +
                                  6x + 4x = 6 + 14                          2   3        3   6
                                                                           6     6   6    30
                                      10x = 20                                −    =    +
                                                                            2    3    3    6
                                        x = 2
                                                                      2(6 )    2 ×     2(6 )    30
                                                                            −        =        +
                                        1
                       2. b.   − 13 =   + 5                           3(2)    2 × 3     2(3)     6
                                        4
                                              1                             3x − 2 = 2x + 5
                              4 x − 13 = 4      x + 5
                                              4                       3x − 2 − 2x = 2x − 2x + 5

                                  4x − 52 = x + 20
                                                                               x − 2 = 5
                                  4x − x = 20 + 52
                                                                               x = 5 + 2
                                      3x = 72
                                                                                 x = 7
                                       x = 24












                                                              47
   47   48   49   50   51   52   53   54   55   56   57